Sociopsychological determinants of career maturity among secondary school students in Osogbo, Osun State, Nigeria - Adeyemo, David Akinlolu; Jegede, D.J (Utan Kayu Publishing, 2023)
The study examined socio-psychological factors' influence on secondary school students' career maturity in Osogbo, Osun state. In view of this, the socio-psychological factors identified in the study include emotional intelligence, career self-efficacy, socio-economic status, gender, academic discipline and occupational prestige. Using a descriptive research survey design 300 secondary school students were selected through simple random sampling techniques from five (5) secondary schools in Osogbo. Standardized instruments were used for data collection in the study; these instruments were however revalidated. Three research questions were answered. The data obtained were analyzed using Pearson Product Moment Correlation (PPMC) and multiple linear regression analysis at 0.05 level of significance. The results indicate that career maturity significantly (positive) correlated with Emotional Intelligence career self-efficacy, socioeconomic status, academic discipline and occupational prestige However, the relationship between gender and career maturity was not significant. When pulled together, the six (6) independent variables significantly affect the student’s career maturity. Besides, each of the independent variables significantly contributed to the prediction of career maturity. Career self-efficacy made the most significant contribution to the criterion, followed by emotional intelligence and socio-economic status. However, occupational prestige, gender and academic discipline did not independently predict the career maturity of secondary school students. Based on the findings, it is recommended that counseling psychologists and other helping professionals should work on assessing and considering emotional intelligence, career self-efficacy, socioeconomic status, occupational prestige and the academic discipline in the process of rendering career guidance to students.